Utilization of Chicken Harvest as a Community Economic Improvement in the Covid-19 Pandemic - Desrina Hardianti; Noprisa Noprisa; Fitria Lestari; Dwi Desmayanasari; Suryatul Aini Asyhara; Retno Dumila; Triyana Dara; Wahyu Alfurosi (Smart Society, 2022)
Â The COVID-19 pandemic has impacted various aspects of people's lives, including the economic sector that occurred in Tanjung Waras Hamlet, Merak Batin Village, RT 15, South Lampung. The observations show the residents' lack of knowledge and creativity in managing the harvest of chicken livestock to improve the creative economy of the residents. Therefore, to maximize this potential, our community service team from the University of Muhammadiyah Lampung assists the community by utilizing chicken harvest to improve the economy. The research method used is qualitative, with activities consisting of preparation, assistance, implementation, evaluation, and monitoring. Data is collected using observation techniques, questionnaires, interviews, and group discussion forums (FGD). This activity was carried out on 6-12 July 2021 in Tanjung Waras Hamlet, Merak Batin Village, RT 15 participants with 20 participants. The results of this activity show that: 1) 90% of respondents succeeded in making frozen food products made from chicken. 2) sales results after being processed into frozen food products provide profits of up to more than 75%. This also makes residents more creative in processing raw chicken pieces into processed products that can provide income and help residents overcome economic problems during the COVID-19 pandemic. Marketing of processed products is carried out by residents from home and also through social media.Â Â